1997
DOI: 10.1063/1.473750
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics over a wide range of temperature (13–744 K): Rate constants for the reactions of CH(ν=0) with H2 and D2 and for the removal of CH(ν=1) by H2 and D2

Abstract: Rate constants were determined for the reactions of CH(X2Π,ν=0) with H2 and D2 and for the relaxation of CH(X2Π,ν=1) by H2 and D2. The method, employing pulsed laser photolysis to generate CH radicals and laser-induced fluorescence to observe their rate of removal, was implemented between 744 and 86 K in heated and cryogenically cooled cells and from 295 to 13 K in a Cinétique de Réaction en Ecoulement Supersonique Uniforme (CRESU) apparatus. The rate constants for the reaction of CH(ν=0) with D2 were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 54 publications
0
47
1
Order By: Relevance
“…It has been observed that the presence of a large excess of argon in the photolysis of methane reduces the quantum yield of H2 formed by 13% [Laufer and McNesby, 1968], and this agrees well with the suppression of process (R5) at high pressure. However, experimental data show that the observed 13% decrease in H2 yield was most probably due to the presence of the reaction CH + H2 + M --> CH3 + M, important only at high total pressures [Brownsword et at, 1997a;Fulle and Hippler, 1997].…”
Section: Chx Fragment Yieldsmentioning
confidence: 93%
“…It has been observed that the presence of a large excess of argon in the photolysis of methane reduces the quantum yield of H2 formed by 13% [Laufer and McNesby, 1968], and this agrees well with the suppression of process (R5) at high pressure. However, experimental data show that the observed 13% decrease in H2 yield was most probably due to the presence of the reaction CH + H2 + M --> CH3 + M, important only at high total pressures [Brownsword et at, 1997a;Fulle and Hippler, 1997].…”
Section: Chx Fragment Yieldsmentioning
confidence: 93%
“…O( 3 P) 39 [44] OH 56 [45] CN 56 [46] CH 56 [47] 1 C 2 ( 1 S g + )57 [48] C 2 N(X 2 P i )54 [49] O 2 13 [11,43] 13 [50] 15 [51] 145 [52] 15 [53] 23 [54] 15 [55] 24 [56] NO 13 [50] 53 [57] 24 [52] 24 [52] 15 [53b, c] 15 [55b] 48 [58] H 2 50 [59] 6 [9] 11 [60] D 2 13 [61] H 2 O50 [62] 50 [63]…”
Section: Neutral-neutral Reactionsmentioning
confidence: 99%
“…Data for k 106 : Grebe and Homann [361], Bohland and Temps [362], Bohland et al [363], Boullart et al [364], Devriendt et al [365], Rohrig et al [358] and Deppe and Wagner [368]. Data derived from measurements of k 106b : Berman and Lin [369], Zabarnick et al [370], Becker et al [371], Brownsword et al [372]. The solid line shows the value used in the present model while the dashed line denotes the recommendation of Baulch et al [26].…”
mentioning
confidence: 99%